Young men's experiences of long-term imprisonment: living life - Tynan, Rachel Rose (Routledge advances in ethnography, 2019)
"Be easy, see whagwan" : introduction -- "My story's boring" : why young prisoners stories matter -- "Real talk" : methodology and reflections on fieldwork -- "Just gotta ride it" : adaptation, survival and change -- "That's just their pen and ink" : resisting the pains of imprisonment -- "Obviously, you can't just back down-- " violence and identity -- "Clothes, food and love-- " : family, fatherhood and the limits of fratriarchy -- "Jail's not gonna do nothin-- at all" : conclusion.